ANALISIS AKUNTANSI PENDAPATAN KONTRAK KONTRAK BERDASARKAN PSAK NO.34 PADA PT. SAMUDRA JAYA LESTARI - Neneng Arum Mia; Sardiyo Sardiyo; Eri Triharyati (LPPM UNIVERSITAS BINA INSAN, 2020)
The purpuse of this study is to determine the recognition of income applied by PT.Samudra Jaya lestari whether it is in accordance with PSAK No.34 ( Revision 2015). Revenue is one of the important elements in information of the elemenst related to the size of the profit earned by company.The method used in this research is in the form of financial statements and work contract letters of PT.Samudra Jaya Lestari and other data in form of literature,articles, journals and websites on the internet.The result of research conducted, namely PT.Samudra Jaya Lestari in applying the income recognition method are not in accordance with the financial statement accounting standards, namely PSAK No.34 regarding constructionservices because PT.Samudra Jaya Lestari has not been consistent in using the income recognition method every year, which should be used in accordance with the provisions that have been applied in PSAK No.34 concerning construction servive revenue.